PRE-SERVICE ENGLISH TEACHER PERCEPTION ABOUT HIGHER ORDER THINKING SKILLS (HOTS) IN THE 21ST CENTURY LEARNING - Fakhomah, Desy Nur; Utami, Melati Sri (Sanata Dharma University Yogyakarta, 2019)
In Indonesia, the consciousness of the significance of HOTs becomes an educational purpose. This study aims to investigate what teachersâ€™ perception and the difficulty in implementing HOTS in 21st century of English language teaching. This research adopted a â€œsequential explanatory mixed methodsâ€ design (Creswell, 2014). It is regarded as explanatory because the initial quantitative data results are explained with the qualitative data. There were 5 participants in total who have volunteered for this study. They are the Pre-service English Teacher of Professional Teacher Program from different universities using randomized sampling. This study indicated that the participants have a high perception in implementing HOTs in the classroom. However, the participants face some difficulties in its implementation, such as time management and studentsâ€™ ability.DOI: doi.org/10.24071/ijiet.2019.030104